Melawan Korupsi: Inspirasi dari Injil Matius 6: 11 - Putra, Andreas Maurenis (Societas Dei: Jurnal Agama dan Masyarakat, 2022)
This theological reflection wants to give a message to Christians by analyzing corruption based on the Gospel of Matthew 6:11 among the corruption proliferation in Indonesia. Through the library method, this article finds that Matthew 6:11 is against corruption because corruption is a form of ignorance to take care the social faith that inherited from Jesus, namely an attitude of being aware and caring for the othersâ€™ needs as reflected for â€œour foodâ€ and â€œenoughâ€ calling. Based on these findings, this article arrives at an alternative solution, it is promoting informal and formal anti-corruption education. Informally, parents are invited to build an example of honest living as a family habit and make the house as a faith school . Formally, it is necessary to integrate anti-corruption values â€‹â€‹into a number of subjects or courses (inclusive approach) and make anti-corruption education into a local content subject or a separated subject (exclusive approach).